2018
DOI: 10.1111/josi.12286
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity Contest Cultures in Policing Organizations and Recommendations for Training Interventions

Abstract: In the wake of the #BlackLivesMatter and #MeToo movements, police conduct has been increasingly scrutinized by the public, especially the use of excessive force, fatal shootings of unarmed civilians, and sexual harassment scandals within policing organizations. Through a review of the policing literature and data collected in a Canadian policing organization, we highlight how masculinity contest culture is related to police misconduct. All four masculinity contest culture dimensions can be observed in policing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 56 publications
3
38
1
Order By: Relevance
“…As one of the first empirical studies to confirm the basic tenets of the masculinity contest culture construct, our findings are noteworthy and generally consistent with related studies reported in this special issue documenting the mostly negative outcomes associated with masculinity contest cultures (Glick et al., ; Rawski & Workman‐Stark, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As one of the first empirical studies to confirm the basic tenets of the masculinity contest culture construct, our findings are noteworthy and generally consistent with related studies reported in this special issue documenting the mostly negative outcomes associated with masculinity contest cultures (Glick et al., ; Rawski & Workman‐Stark, ).…”
Section: Discussionsupporting
confidence: 91%
“…Initial research shows that masculinity contest cultures correlate with a host of negative outcomes, ranging from organizational‐level perceptions and behaviors (e.g., lower psychological safety, more bullying and harassment) to individual‐level attitudes and outcomes (e.g., burnout, turnover intentions) (Glick, Berdahl, & Alonso, ; Rawski & Workman‐Stark, ). However, much remains unknown about the workplace characteristics that exacerbate and attenuate masculinity contest cultures’ effects on individuals and the organizations who employ them.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…As expected, masculinity contest norms tended to be strongly correlated with other organizational‐level measures (other culture measures and dominance behaviors from coworkers), moderately correlated with measures of individuals’ relationship to work, and weakly correlated with personal outcome measures such as general psychological or physical health. Similar results (with the MCC relating to negative workplace culture and outcomes) have been obtained by Rawski and Workman‐Stark () within a police organization and Matos, O'Neill, and Lei () in a general worker sample (we review unanticipated effects found by Matos et al. in detail below).…”
Section: Discussionsupporting
confidence: 84%
“…We are encouraged by Rawski and Workman‐Stark's () research using the MCC within a single police organization. In their sample (which included both police officers and civil employees), MCC scale scores, similar to results obtained in our two samples, correlated with other negative culture and workplace behavior measures (less inclusive culture and leadership, less organizational justice, lower psychological safety) and worse personal outcomes (less organizational dedication, lower job satisfaction, and poorer well‐being).…”
Section: Discussionmentioning
confidence: 99%
“…This introductory article outlines a theoretical framework for thinking about MCCs. Subsequent papers in this special issue represent initial studies into measuring MCCs (Glick et al., ), assessing their consequences (Alonso, ; Glick et al., ; Matos, O'Neill, and Lei, ; Reid, O'Neill & Blair‐Loy, ; Rawski & Workman‐Stark, ), analyzing their ideological underpinnings (Kuchynka, Bosson, Vandello, & Puryear, ; Munsch, Weaver, Bosson, & O'Connor, ), and considering potential interventions (Ely & Kimmel, ; Rawski & Workman‐Stark, ).…”
mentioning
confidence: 99%